2006
DOI: 10.1111/j.1365-2214.2006.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet addiction among Chinese adolescents: prevalence and psychological features

Abstract: The present study suggests that Internet addiction is not rare among Chinese adolescents. In addition, adolescents with Internet addiction possess different psychological features when compared with those who use the Internet less frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
294
1
21

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 446 publications
(368 citation statements)
references
References 18 publications
35
294
1
21
Order By: Relevance
“…Video game addiction has been found to be positively related to Neuroticism (Charlton & Danforth, 2010;Huh & Bowman, 2008;Mehroof & Griffiths, 2010;Peters & Malesky, 2008) and Extroversion (Huh & Bowman, 2008), and negatively related to Extroversion (Peters & Malesky, 2008), Agreeableness (Collins, Freeman & Chamarro-Premuzic, 2012;Peters & Malesky, 2008) and Conscientiousness (Peters & Malesky, 2008). A related addiction is Internet addiction or problematic Internet use, which in several studies has been associated with Neuroticism (Cao & Su, 2007;Öztürk & Özmen, 2011;Serin, 2011;Tsai et al, 2009). In one study, Internet addiction was negatively associated with Extroversion and Conscientiousness (Gnisci, Perugini, Pedone & Di Conza, 2011) whereas Serin (2011) found it to be positively associated with Extroversion.…”
Section: Introductionmentioning
confidence: 99%
“…Video game addiction has been found to be positively related to Neuroticism (Charlton & Danforth, 2010;Huh & Bowman, 2008;Mehroof & Griffiths, 2010;Peters & Malesky, 2008) and Extroversion (Huh & Bowman, 2008), and negatively related to Extroversion (Peters & Malesky, 2008), Agreeableness (Collins, Freeman & Chamarro-Premuzic, 2012;Peters & Malesky, 2008) and Conscientiousness (Peters & Malesky, 2008). A related addiction is Internet addiction or problematic Internet use, which in several studies has been associated with Neuroticism (Cao & Su, 2007;Öztürk & Özmen, 2011;Serin, 2011;Tsai et al, 2009). In one study, Internet addiction was negatively associated with Extroversion and Conscientiousness (Gnisci, Perugini, Pedone & Di Conza, 2011) whereas Serin (2011) found it to be positively associated with Extroversion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in their study adolescents with internet addiction possess had different psychological features when compared with those who use the internet less frequently [15]. Shaw and Black reported that prevalence of internet addiction in general US population by random telephone survey was 0.3-0.7 % [16].…”
Section: Discussionmentioning
confidence: 99%
“…Those with Internet addiction tendencies are known to not manage time efficiently and to spend most of their time on the Internet. In research comparing 64 Internet addicted and 64 non-addicted adolescents, the Internet addicts were less successful at managing time (Cao & Su, 2007). Intervention programs with proven efficacy include activities related to time management, such as regulating time spent on the Internet and planning daily activities (Kim, 2008;Odacı & Çelik, 2011;Young, 2007).…”
Section: Discussionmentioning
confidence: 99%